Pengaruh pengembangan karir dan lingkungan kerja non fisik terhadap retensi karyawan - Qomariah Imelda, Dewi; Budiarti, Ika Niswatin (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
It is important for companies to recognize that employee retention is an ongoing focus when it comes to HR. Therefore, companies need to make various efforts to retain their employees. This study aims to analyze the influence of the variables career development, non-physical work environment, and organizational commitment on employee retention. In this study, statistical analysis was carried out to determine the partial positive effect of each independent variable on the dependent variable. The results of the analysis show that the career development variable has a partial positive effect on employee retention. Likewise, the non-physical work environment variable also has a partial positive effect on employee retention. Furthermore, the organizational commitment variable also shows a partial positive effect on employee retention. This research provides a better understanding of the importance of increasing career development, non-physical work environment, and organizational commitment to increase employee retention rates. The practical implication of this research is that organizations need to pay attention to these factors when designing policies and programs that can increase employee retention.